(untitled) (Third Sector Social Economic Review, 2024)
This study aims to evaluate the appropriateness of academic articles on green reconciliation in Turkey using bibliometric methods. Within the framework of the study, the Dergipark database, which provides electronic hosting and editorial process management services for academic refereed journals published in Turkey, was used as the research population. The articles in the system were examined and analysed using various bibliometric indicators. The analysis included criteria such as distribution of articles by years, institutional affiliations of authors, journal indexes, number of authors and number of citations. According to the study, the European Green Deal is a process with both opportunities and challenges for Turkey. In Turkey, academic studies on the issue generally focus on economic, environmental and social impacts, but there are gaps in areas such as long-term impacts and structural reforms. In particular, analyses of energy policy, the green economy and the social dimension should be developed further and should be based on concrete recommendations. There is also a lack of representation in the international literature and a limited number of publications. Interdisciplinary cooperation and practical studies are crucial for the effective implementation of the Green Deal in Turkey.